Pancreatic cystosis: A rare pancreatic manifestation in cystic fibrosis - Mohammad A. Wazzan, (Universiti Kebangsaan Malaysia, 2015)
Cystic fibrosis (CF) is a multisystemic, autosomal recessive disorder that predominantly affects infants, children, and young adults. Manifestations of CF involve the lung and gastrointestinal tract, including the pancreas. Pancreatic cystosis is a rare condition typically seen in CF during the second decade of life. It has characteristic magnetic resonance imaging (MRI) and ultrasound (US) features. A large cystic mass replacing the pancreas has been found by US and MRI study carried out as a part of clinical workup for a 17-year-old girl, known to have CF and presented with epigastric pain and a palpable mass. There was no history of trauma or clinical evidence of pancreatitis. On the basis of MRI findings and the patient age, a radiological diagnosis of pancreatic cystosis is securely made. Biopsy should be preserved for those who have atypical presentation.